Domain expertise and the effectiveness of dynamic simulator interfaces in the acquisition of procedural motor skills. (6th August 2012) - Akinlofa, Olurotimi R.; Holt, Patrik O'Brian; Elyan, Eyad
Abstract: Previous research into the effectiveness of dynamic versus static instructional design paradigms has reported divergent findings. Dynamic instructions have been shown to be more effective in teaching novel procedural skills. In contrast, the apparent benefit of dynamic over static instructions has been attributed in other studies to the cognitive capabilities and previous knowledge of the learner. Can the benefit of dynamic instruction persist in learners with domain expertise on learning novel tasks? In this paper, we report the result of an experiment that shows that irrespective of the learner's previous knowledge, dynamic instructions retain a significant effectiveness over statics for teaching intra‐domain novel task performance. Twenty‐four participants with domain expertise were divided into three independent groups to perform a procedural motor task following treatment with different training interfaces. After controlling for spatial abilities and excluding previous specific‐to‐task knowledge, we observe that participants that trained with interfaces containing dynamic content recorded better task performance measures than others using non‐dynamic interfaces. This suggest that within the context of motor skill acquisition, dynamic instructional interfaces can yield significant increases to post‐learning task performance measures, which is independent of the learner's cognitive capabilities or previous knowledge.